2022
DOI: 10.3390/ijms23073584
|View full text |Cite
|
Sign up to set email alerts
|

Lp(a) and the Risk for Cardiovascular Disease: Focus on the Lp(a) Paradox in Diabetes Mellitus

Abstract: Lipoprotein(a) (Lp(a)) is one of the strongest causal risk factors of atherosclerotic disease. It is rich in cholesteryl ester and composed of apolipoprotein B and apo(a). Plasma Lp(a) levels are determined by apo(a) transcriptional activity driven by a direct repeat (DR) response element in the apo(a) promoter under the control of (HNF)4α Farnesoid-X receptor (FXR) ligands play a key role in the downregulation of APOA expression. In vitro studies on the catabolism of Lp(a) have revealed that Lp(a) binds to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
9
0
2
Order By: Relevance
“…Our result indicated that the correlation between LP(a) serum level and PAD severity was not observed in patients with DM history. Surprisingly, researchers have proposed that DM patients always have reduced Lp(a) levels 28 . We speculated that the existence of DM might have some influence on the function of LP(a), thus concealing the relation between LP(a) serum level and PAD.…”
Section: Discussionmentioning
confidence: 89%
“…Our result indicated that the correlation between LP(a) serum level and PAD severity was not observed in patients with DM history. Surprisingly, researchers have proposed that DM patients always have reduced Lp(a) levels 28 . We speculated that the existence of DM might have some influence on the function of LP(a), thus concealing the relation between LP(a) serum level and PAD.…”
Section: Discussionmentioning
confidence: 89%
“…The recent studies indicated that higher Lp(a) level was associated with subclinical coronary atherosclerosis in asymptomatic subjects ( 42 ), and elevated baseline Lp(a) was associated with subclinical vascular and valvular calcification in the White and Black participants ( 43 ). It is known that Lp(a) and its associated oxidized phospholipids could induce a proinflammatory response, causing cellular apoptosis and necrosis which accelerate necrotic core formation ( 44 , 45 ). Furthermore, Lp(a) contains proatherogenic components of LDL, and its prothrombotic effects through the plasminogen-like apolipoprotein(a) also contribute to the atherosclerosis ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are conflicting data published, the majority of studies found that individuals suffering from type-2 diabetes mellitus (T2DM) or metabolic syndrome indeed exhibit lower plasma Lp(a) as compared with healthy controls [47]. We recently reviewed this topic in more detail and came to the following conclusions [48]:…”
Section: Burning Questions To Be Addressedmentioning
confidence: 99%
“…There remains still a large fraction of patients with T2DM exhibiting reduced levels of Lp(a) in whom mutations in transcription factors have not yet documented. Part of them might relate to altered metabolism of triglyceride-rich lipoproteins as suggest by Skoumas et al [47], yet there remain still numerous questions with respect to the pathophysiology of the ‘Lp(a) paradox in diabetes mellitus’ [48].…”
Section: Burning Questions To Be Addressedmentioning
confidence: 99%
See 1 more Smart Citation